Is the Prosperity Gospel Biblical? A Critique in Light of Literary Context and Union with Christ - Ellington, Dustin W. (In Search of Health and Wealth: The Prosperity Gospel in African, Reformed Perspective, 2014)
This essay seeks to advance the dialogue about the prosperity gospel in two ways. First, the essay challenges the sides of the debate to go beyond hurling biblical proof texts back and forth at each other. It argues that teaching on the Christian life must be supported by the main aims and themes of biblical books and the canon as a whole, rather than being based only on scattered individual verses. Second, building upon the first argument, the essay critiques the message of prosperity by addressing its neglect of one of the New Testament’s most prevalent themes: union with Christ. Concentrating on the thought of Paul in 1-2 Corinthians, the essay demonstrates that because of believers’ union with Christ, the Christian life embodies the message of Christ crucified for others. This participation in Christ and embodiment of his sacrifice for others requires that believers live not for themselves but on behalf of Christ and others. Therefore we cannot guarantee that the Christian life leads individuals to material wealth.
free
Keywords: Religion / Christian Church / General; Religion / Christian Theology / General; Religion / Christianity / Denominations